Inheritance Pattern of Lip Prints and Blood Group among Parents and their Offspring in Javanese Population, Indonesia for Assisting Forensic Identification - Agung Sosiawan1 , Cahyo Pulunggono1 , Arofi Kurniawan1 , Haryono Utomo1 , Maria Istiqomah Marini1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lip prints and bloodstains may be left behind in many crime scenes and may reveal the identity of the victimand the suspected person. This study was aimed to investigate the inheritance pattern of lip prints and bloodgroups among parents and their offspring in the Javanese population. 105 subjects from 25 Javanese familyframes participated in this study. Lips print pattern was recorded and analyzed according to Suzuki andTsuchihashi classification. A blood group test was also performed for each subject. The statistical analysiscarried out using IBM® SPSS® Statistics version 23.0 (IBM, Armonk, New York, USA). The results of thisstudy revealed that type II was the predominant pattern of lip prints among the Javanese population (34.3%).Blood group A was the predominant type in subjects with lip prints type II (15%). The result also shows thatthe lip prints pattern in girls tends to be inherited from the mother. However, the inheritance of lip printspattern in boys couldn’t be determined precisely. The heritability of lip prints pattern was observed betweenparents and their offspring. Also, there was a tendency of blood groups to have a certain pattern of lip prints.